Unveiling The Perception of Safety Culture on Incident Reporting at Siloam Hospitals Kebon Jeruk: A Qualitative Study - Vinny Agatha; Alice Yvonne Yovita Pangemanan (Journal of Comprehensive Science, 2026)
Patient safety culture and incident reporting are important components in maintaining quality of care and safety in hospitals. However, their implementation often faces challenges, especially regarding the involvement of health workers in the reporting process. This study aims to identify and analyze the safety culture, challenges, and factors that influence incident reporting at Siloam Kebon Jeruk Hospital. This study used a qualitative approach with a semi-structured interview method with health workers in various service units. Data were thematically analyzed to gain an in-depth understanding of participants' experiences and perceptions. The results showed that safety culture has been integrated into the hospital system, but there are still variations in understanding and implementation in the field. Factors influencing incident reporting included leadership, non-punitive policies, workload, understanding of the reporting system, and support from direct supervisors. Key challenges included time constraints, access to the reporting system, and concerns about the impact of reporting. Hospitals need to strengthen education, provide flexible and accessible reporting systems, and build a reporting culture based on equity and collaboration. Managerial support and incentivization may also be strategies to increase staff participation in incident reporting.